Estimating the prevalence of diabetes mellitus and thyroid disorders using medication data in Flanders, Belgium. (16th July 2017) - Vaes, Bert; Ruelens, Catherine; Saikali, Samuel; Smets, Alexander; Henrard, Séverine; Renard, Francoise; van den Akker, Marjan; Van Pottelbergh, Gijs; Goderis, Geert; Van der Heyden, Johan
Abstract: Background: Various methods exist to estimate disease prevalences. The aim of this study was to determine whether dispensed, self-reported and prescribed medication data could be used to estimate the prevalence of diabetes mellitus and thyroid disorders. Second, these pharmaco-epidemiological estimates were compared with prevalences based on self-reported diagnoses and doctor-registered diagnoses. Methods: Data on medication for diabetes and thyroid disorders were obtained from three different sources in Flanders (Belgium) for 2008: a purely administrative database containing data on dispensed medication, the Belgian National Health Interview Survey for self-reported medication and diagnoses, and a patient record database for prescribed medication and doctor-registered diagnoses. Prevalences were estimated based on medication data and compared with each other. Cross-tabulations of dispensed medication and self-reported diagnoses, and prescribed medication and doctor-registered diagnoses, were investigated. Results: Prevalences based on dispensed medication were the highest (4.39 and 2.98% for diabetes and thyroid disorders, respectively). The lowest prevalences were found using prescribed medication (2.39 and 1.72%, respectively). Cross-tabulating dispensed medication and self-reported diagnoses yielded a moderate to high sensitivity for diabetes (90.4%) and thyroid disorders (77.5%), while prescribed medication showed a low sensitivity for doctor-registered diagnoses (56.5 and 43.6%, respectively). The specificity remained above 99% in all cases. Conclusions: This study was the first to perform cross-tabulations for disease prevalence estimates between different databases and within (sub)populations. Purely administrative database was shown to be a reliable source to estimate disease prevalence based on dispensed medication. Prevalence estimates based on prescribed or self-reported medication were shown to have important limitations.